Barrier and facilitators in implementing household waste management program in West Kotawaringin - Kurniawan, Muhammad Chamim Thohari; Sutena, Marthinus; Padmawati, Retna Siwi (Universitas Gadjah Mada, 2022)
Purpose: This study aims to evaluate the program at South Arut District to explore barriers and facilitators in the household waste management program. Methods: This qualitative case-explanatory study used a thematic analysis approach. Thirteen respondents were the environmental service chair, the health office, the sub-district of South Arut, the cleaning staff (2 people), the Yayorin manager (NGO), restaurant owners, farmers, fishers, Aisyiyah, Bawi Dayak, Culture and Tourism Association, student, head of RT 15, and household member with at least three years residence in Pangkalan Bun. Results: The parties forming regulations are the Environment Service, Public Works Service, South Arut Sub-district, kelurahan, and village heads. The budget is 21 billion rupiahs. Program coordinators in each unit are still not optimal in managing activities that can produce marketable outputs. The strategies are socialization, distributing pamphlets, and broadcasting broadcasts on regional television channels. The inhibiting factor is the perception of people who do not care about the environment and lack infrastructure. The driving factor is the self-awareness of people who care about environmental cleanliness. Conclusion: Local governments need to consider having an executive manager and operational management team in each unit who can add the necessary infrastructure and closely monitor implementation, which will maximize the production process with marketable products. Also, the management team must promote the utilization of the waste management system to the community.